An Analysis of Studentâ€™s Difficulties in Learning Mathematics at Madrasah Ibtidaiyah - Atin Supriatin; Aeni Latifah; Siti Annisah (Al Ibtida: Jurnal Pendidikan Guru MI, 2023)
AbstractThis study aims to describe the level of difficulty of students in solving story problems in mathematics learning at Madrasah Ibtidaiyah. This research is a descriptive-analytical study. The participants of the study were third-grade students at one Madrasah Ibtidaiyah in Palangka Raya City, which numbered 34 people and fifth-grade students at one Ibtidaiyah Madrasah in East Lampung City, which amounted to 40 people. Data collection techniques use tests in the form of 10 questions. The tests given to the research sample have met the criteria of validity and reliability. Data analysis techniques use descriptive statistics in the form of tables and graphs through the calculation of averages and percentages. The results of this study explain that, in general, students have difficulty solving story problems. The most difficulty experienced by third graders is associating mathematics with daily life problems, which is 83.82%. In comparison, the most difficulty experienced by fifth-grade students is changing the language of everyday problems into the language of mathematics (making mathematical models or making a solution plan), which is 82%. This research produced a novelty in describing the difficulty of students solving story problems in mathematics learning by linking mathematics to daily life problems in Madrasah Ibtidaiyah.Keywords: analysis of difficulty levels, story problems, mathematics learning.Â AbstrakPenelitian ini bertujuan untuk mendeskripsikan tingkat kesulitan siswa dalam memecahkan masalah cerita dalam pembelajaran matematika di Madrasah Ibtidaiyah. Penelitian ini merupakan penelitian deskriptif analitis. Subjek penelitian adalah siswa kelas III Madrasah Ibtidaiyah Kota Palangka Raya yang berjumlah 34 orang dan siswa kelas lima Madrasah satu Madrasah Kota Lampung Timur yang berjumlah 40 orang. Teknik pengumpulan data menggunakan tes berupa 10 pertanyaan. Tes yang diberikan kepada sampel penelitian telah memenuhi kriteria validitas dan reliabilitas. Teknik analisis data menggunakan statistik deskriptif berupa tabel dan grafik, melalui perhitungan rata-rata dan persentase. Hasil penelitian ini menjelaskan bahwa pada umumnya siswa mengalami kesulitan dalam memecahkan masalah cerita. Kesulitan yang paling banyak dialami oleh siswa kelas tiga adalah mengaitkan matematika dengan masalah kehidupan sehari-hari, yaitu 83,82%. Sedangkan kesulitan yang paling banyak dialami oleh siswa kelas V adalah mengubah bahasa soal sehari-hari menjadi bahasa matematika (membuat model matematika atau membuat rencana solusi) yaitu 82%. Penelitian ini menghasilkan kebaruan berupa deskripsi kesulitan siswa memecahkan masalah cerita dalam pembelajaran matematika dengan mengaitkan matematika dalam masalah kehidupan sehari-hari di Madrasah Ibtidaiyah.Kata kunci: analisis tingkat kesulitan, permasalahan cerita, pembelajaran matematika.